BEYOND THE WATERS, THE NORTHEAST DISCUSSION OF SÃO FRANCISCO RIVER - Lima, Luiz Cruz (Revista do Departamento de Geografia, 2011)
This work presents a synthesis of the history of the Project of Water Transposition from São Francisco River to the basins on the northern part of Northeast. Those works aim to assure water supply during the dry periods, for men and animals. Besides indicating the historical way of that transposition, the text lists the social impacts from the environmental changes. Finally, it deals with new water geography, adopting the model of the human action on nature proposed by Milton Santos.